Effect of nitrogen and zinc management on growth, yield and economics of bread wheat (Triticum aestivum) varieties - ARIF, MOHD; DASHORA, L N; CHOUDHARY, J; KADAM, S S; MOHSIN, MOHAMMED (The Indian Journal of Agricultural Sciences, 2019)
Field experiments were conducted during rabi season of 2016–17 and 2017–18 at Udaipur (Rajasthan) to study the effect of nitrogen and zinc management on growth, yield and economics of different wheat (Triticum aestivum L.) varieties. The treatments consisted of four wheat varieties, viz. Raj 4120, Raj 4037, Raj 4079 and Raj 4238 in main plots and seven nutrient management treatments, viz. 100% RDN, 100% RDN + ZnSO4 25 kg/ha soil application, 100% RDN + ZnSO4 0.5% foliar spray, 100% RDN + ZnSO4 25 kg/ha soil application + ZnSO4 0.5% foliar spray, 125% RDN + ZnSO4 25 kg/ha soil application, 125% RDN + ZnSO4 0.5% foliar spray and 125% RDN + ZnSO4 25 kg/ha soil application + ZnSO4 0.5% foliar spray in sub plots. The study of different wheat varieties indicated that highest values of growth parameters, yield attributes, grain yield (5707 kg/ha), straw yield (8869 kg/ha) and biological yield (14576 kg/ha), and net returns (` 86255/ha) and B:C ratio (2.36) were recorded with wheat variety Raj 4037. Further, application of treatment 125% RDN + ZnSO4 25 kg/ha soil application + ZnSO4 0.5% foliar spray recorded significantly higher values of growth parameters, yield attributes, grain yield (5681 kg/ha), straw yield (8265 kg/ha) and biological yield (13946 kg/ha), and net returns (` 83230/ha).